A POSTCOLONIAL ANALYSIS OF STELLA DADZIE’S A KICK IN THE BELLY - Daiyatun Nazah, Trisna Silvi; cindy cahyani; Mahrunnisa Nur Utari; Thesa Izfadliillah (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2024)
This research explores the various forms of violence and oppression endured by enslaved Black women in the Caribbean and the Americas as depicted in Stella Dadzie's A Kick in the Belly. Using a postcolonial feminist approach, this study identifies five forms of violence - physical, psychological, sexual, systemic, and cultural, that were deliberately employed to uphold colonial domination over Black women. These forms of violence were not only tools of control but also mechanisms to sustain both racial and gender hierarchies within the colonial system. Employing a descriptive qualitative method, this research relies on documentation as its primary instrument for analyzing the historical and literary narratives presented in Dadzie’s work. The study highlights the collective trauma experienced by enslaved Black women and illustrates how violence was systematically used to reinforce their subjugation. Furthermore, this research underscores the resilience and resistance of these women against oppressive structures, shedding light on their agency despite immense adversity. The findings of this research contribute to a broader understanding of the historical roots of racial and gender-based violence. Moreover, it establishes a connection between historical oppression and contemporary social movements advocating for racial justice and women’s rights, reinforcing the continued relevance of addressing systemic inequalities in today’s society.